(untitled) (Південний архів (історичні науки), 2023)
Purpose. The article describes photos from Tcherikower’s collection about the anti-Jewish pogroms in Chornobyl. Photographs act as markers of temporality: attention is drawn to the circumstances of their creation; the use of these photos as documentary evidence and violence during the anti-Jewish pogroms, by Jewish organizations and the archiving of photos as part of Mizrakh Yidisher Historisher Arkhiv Сollections in the YIVO Institute for Jewish Research (The Center for Jewish History). Research methods. The methods of archival heuristics and description, interdisciplinary approaches were used, in particular the concept of «temporality» in historical science to determine the time markers of an era in this case, the anti-Jewish pogroms, the photos of which flew around the world and determined politics, influenced social relations, became a collective part of historical memory. Research results. An attempt was made to classify collection about the anti-Jewish pogroms in Chornobyl, to detail the descriptions, the history of the creation of this collection and their significance through the concept of temporality in historical science is described. Conclusions. Tcherikower’s photo collection about Chornobyl is a unique collection of images depicting events related to the establishment of power in the Chornobul’s region by Otaman Struk and anti-Jewish pogroms. At the center of the photo selection is Otaman Struk, his army and his victims. Time markers are the traditions of self-images that date back to the First World War and are part of the worldview of the military of that time, even if it is a private army that owns a small territory, such as Struk’s. It is a display of weapons that is supposed to assert masculinity, even children and teenagers are photographed with weapons. Although the soldiers have poor clothing, they are well armed. It is also a depiction of rituals showing respect for the dead: funerals of fallen soldiers, victims of pogroms. The depictions of victims and victims are as lifelike and detailed as possible; they contain inscriptions in French, and were apparently used by Tcherikower during the Schwarzbard trial. The collection of photos also demonstrates the work of investigating anti-Jewish pogroms: visiting cemeteries with the graves of the murdered, destroyed houses, interviewing the victims and their relatives, collecting photographs from before life.